Pengaruh digital marketing terhadap peningkatan pendapatan Usaha Mikro Kecil dan Menengah di Kecamatan Plosoklaten - Fadzilasani, Maulida Fiha; Retnasih, Nora Ria (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to examine digital marketing practices carried out by Micro, Small and Medium Enterprises and their impact on revenue. The research method used is a combination of quantitative and qualitative methods with the research object being MSMEs in Klaten District, Kediri Regency, East Java. The research findings are that the majority of MSMEs use the Whatsapp, Facebook and Instagram platforms to market products. The majority of MSME business owners are between 20-25 years old. MSMEs in Plosoklaten District generally focus on food businesses. The use of Whatsapp, Facebook and Instagram helps MSMEs promote products and attract potential customers. Thus, digital marketing through these platforms has a significant influence in increasing the income of MSMEs in Plosoklaten District, especially in food businesses.